2011
DOI: 10.1111/j.1365-2788.2011.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysing family service needs of typically underserved families in the USA

Abstract: Findings underscore the need for resources to empower families and the value of using the FQOLS-2006 to ascertain the service support needs and strengths of families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
(79 reference statements)
3
28
0
5
Order By: Relevance
“…Lack of awareness is one of the main barriers that family caregivers face in accessing support services, similar to past studies on families of persons with developmental disabilities (Burnette, 1999;Kalyanpur & Rao, 1991;Samuel, Hobden, LeRoy & Lacey, 2012).…”
Section: Service Professionalsmentioning
confidence: 57%
“…Lack of awareness is one of the main barriers that family caregivers face in accessing support services, similar to past studies on families of persons with developmental disabilities (Burnette, 1999;Kalyanpur & Rao, 1991;Samuel, Hobden, LeRoy & Lacey, 2012).…”
Section: Service Professionalsmentioning
confidence: 57%
“…A closer analysis of the participants’ descriptions of these problems, however, indicates that most were not able to describe or state their grandchild’s diagnosis or type of disability. In the case of autism spectrum disorders (ASD), for example, only 5 (1.34%) of the 372 grandparents who responded to the open-ended question designed to elicit data on the grandchild’s diagnosis reported that at least one of their grandchildren had an ASD, in contrast to research based on convenience samples from metro Detroit that have indicated a higher parent-reported incidence of ASD (Samuel et al, 2011 & 2012). National and state-level data also indicate that ASD is the fastest growing developmental disability, resulting in long waits to obtain services (Boyle et al, 2011; Jones et al, 2016; Michigan ASD State Plan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…L'importance de donner de l'information sur les services a été relevée dans de nombreuses études (Chinn & Homeyard, 2017;King, Williams & Hahn-Goldberg, 2017;Mitchell & Sloper, 2002;Samuel, Hobden, Leroy & Lacey, 2012). Être informé correspond à un besoin identifié par les parents qui reçoivent des services pour leur enfant (Leblanc, Robert & Boyer, 2013).…”
Section: Le Besoin D'être Informé Sur Les Servicesunclassified
“…L'information constitue un besoin fondamental (King et al, 2017). Or, malgré la volonté des organisations de bien informer leurs utilisateurs, il semble que l'information sur les services est souvent obtenue de façon informelle ou par l'entremise des autres familles ou des amis, plutôt que par les professionnels de l'organisation (Girard, Miron & Couture, 2014;O'Reilly, Karim & Lester, 2014;Redmond & Richardson, 2003;Samuel et al, 2012), et parfois, les informations sont acquises par hasard, sans démarche systématique de la part des organisations qui les desservent (Hayles, Harvey, Plummer & Jones, 2015).…”
Section: Le Besoin D'être Informé Sur Les Servicesunclassified